The Role of Village Government in Achieving Village Without Poverty - Sinarwati, Ni Kadek; Eka Putra, I Komang; Rona, I Wayan (UPT Publikasi Ilmiah (Universitas Islam Bandung), 2023)
This study aims to describe the achievements, roles of village governments, supporting factors, obstacles and work plans of the village government to accelerate the achievement of villages without poverty in Antiga Kelod Village. This type of research was qualitative descriptive, with primary and secondary data. The method of data collection were observation, documentation and in-depth interviews. Research informants were village government, poor people, local assistants and BUMDEs managers. The results showed that the achievement of villages without poverty was 70.45 percent, in the good category. The role of the village government was carried out by intensifying the village's cash-intensive program, the partitioning of villagers' and food security programs. Supporting the achievement were the existence of BUMDes, livestock farmer groups, village funds and social capital. The obstacle to achievement was villagers who were reluctant to be excluded from the data of the poor. The village government's work plan to accelerate the achievement of a village without poverty is to develop the village's tourism potential. The village government was advised to take a persuasive approach to villagers who were reluctant to be excluded from the data of the poor.